Pengaruh Model Kooperatif Tipe Course Review Horay Pada Hasil Belajar Siswa Mata Pelajaran IPS Kelas VI SD Negeri 13 Pasar Kambang - Winda Anjelina; Firman Firman; Desyandri Desyandri (Universitas Mathla'ul Anwar Banten, 2021)
This study was to see whether there was an effect of the CRH-type cooperative model on social studies learning outcomes in grade VI SD. This type of research is